Tabula Imperii Romani. Castra Regina, Vindobona, Carnuntum, Praha 1986 - Hatłas, Jerzy (Balcanica Posnaniensia. Acta et studia, 1990)
Hatłas Jerzy, book review: Tabula Imperii Romani. Castra Regina, Vindobona, Carnuntum, Academia, Praha 1986, „Balcanica Posnaniensia. Acta et Studia” 1990, t. 5, s. 446–447.